Correction: Beyond eves and cracks: An interdisciplinary study of socio-spatial variation in urban malaria transmission in Ethiopia. - Claudia Nieto-Sanchez; Stefanie Dens; Kalkidan Solomon; Asgedom Haile; Yue Yuan; Thomas Hawer; Delenasaw Yewhalaw; Adamu Addissie; Koen Peeters Grietens (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pgph.0000173.].